Combinatorial Optimization and Applications 9th International Conference, COCOA 2015, Houston, TX, USA, December 18-20, 2015, Proceedings - Lu, Zaixin; Kim, Donghyun; Wu, Weili; Li, Wei; Du, Ding-Zhu (Theoretical Computer Science and General Issues,, 2015)
This book constitutes the refereed proceedings of the 9th International Conference on Combinatorial Optimization and Applications, COCOA 2015, held in Houston, TX, USA, in December 2015. The 59 full papers included in the book were carefully reviewed and selected from 125 submissions. Topics covered include classic combinatorial optimization; geometric optimization; network optimization; applied optimization; complexity and game; and optimization in graphs.